Drink with the addition of whey and prebiotic dietary fiber - Bosi, Mirela Guedes; Bernabé, Bruna Magnago; Della Lucia, Suzana Maria; Roberto, Consuelo Domenici (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the sensorial acceptance of non‑fermented drink with addition of inulin and acerola pulp. Six beverage formulations were developed with addition of 0, 20, 40, 60, 80, and 100% whey. Whey pH was 6.59, and its acidity was 0.103% lactic acid. A nine‑point hedonic scale was used for the acceptance test. Hedonic means of samples with 0, 20, and 40% whey did not differ significantly and varied between 6 and 8. Developed beverages with up to 60% whey are good alternatives for harnessing this byproduct in milk companies.
Keywords: whey utilization; sensory acceptance; inulin